Development of a Rare Flora and Fauna Booklet on the Toba Caldera to Enhance the Knowledge Dimension of Ecoliteracy among Senior High School Students - Yusnidar Sihombing; Binari Manurung; Ashar Hasairin (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to examine the feasibility and effectiveness of a booklet on the rare flora and fauna of the Toba Caldera as instructional material for biodiversity topics. The study employed a Research and Development (R&D) approach using the 4D model, which consists of the Define, Design, Develop, and Disseminate stages. The feasibility of the booklet was assessed based on expert validation, teacher responses, and student responses, while its effectiveness was evaluated using the Mann–Whitney test and N-Gain analysis. The feasibility results indicated that the booklet was categorized as very good based on expert validation. Teacher responses were also rated very good, with a score of 96.25%, and student responses in each trial likewise fell within the very good category. The effectiveness test conducted on students at SMAN 1 Lumban Julu showed an N-Gain value of 0.68, which was categorized as moderate. The Mann–Whitney test indicated a significant difference in ecological literacy knowledge between the experimental and control classes on the posttest, with a probability value of 0.00 < 0.05. In addition, students’ biodiversity ecoliteracy knowledge reached 86.64%, which was classified as high. Therefore, the developed booklet is effective in improving students’ ecological literacy knowledge and is feasible for use as a supplementary teaching material in biodiversity learning by utilizing local potential as a learning resource.